Teaching Prediction Strategy on Students’ Achievement in Listening Comprehension - Harahap, Yunita Mutiara; Rangkuti, Linda Astuti; Lubis, Sofia Idawati (English Teaching and Linguistics Journal, 2021)
The objective of this research was to find out if Prediction Strategy significantly affected students’ achievement in listening comprehension. The design applied in this research was experimental research design. This research was conducted at SMK Teladan Indrapura Batubara. The population of this research was 70 students from the two parallel classes; X TKJ-1 and X TKJ-2. Random sampling technique was employed in taking the sample and 60 students were chosen as the sample. X TKJ-1 was selected as the experimental group and X TKJ-2 was selected as the control group. The experimental group was taught by using Prediction Strategy while the control group was taught by conventional strategy. The instrument used to collect the data was multiple-choice test consisted of 40 items. The data were analyzed by using t-test formula. After the data analysis, it was obtained tobserved value was higher than that of ttable (6.13 > 2.00) with the degree of freedom df = 58 at the level of significance α = 0.05. It meant that Ha was accepted and Ho was rejected. In conclusion, Prediction Strategy significantly affected students’ achievement in listening comprehension.